Illness, the overlooked research topic for time-loss in women`s football - a scoping review - Wang, A.; Koh, B.; McCall, A.; Ferrer, E.; Mehta, R.; Okholm Kryger, K. (Research in Sports Medicine, 2024)
The best medical care for female football athletes should be evidence-based, and patient- and context-specific. A 2019 scoping review identified key knowledge gaps relating to the health of female footballers. Since then, research in women`s football has been intensifying. To aid in the direction of future research, this study aims to scope peer-reviewed, illness-related research in women`s football. Five databases were searched in July 2023. In combination with identified studies from the 2019 review, 72 studies were included for data extraction of sample characteristics (age, playing level, geography), illness characteristics according to IOC guidance, and broader research themes. Results reveal an overall lack of quantity and variety in illnesses investigated, with a growing popularity in mental health research. Minimal female athlete-specific illnesses were identified. Future research must address urgent female-specific illness topics, and also consider where knowledge from adjacent populations might be safe to adapt into women`s football.